Against Latour – On the Questionable Foundations of Post-Critical Pedagogy - Haker, Christoph; Otterspeer, Lukas (On Education. Journal for Research and Debate)
Critique has run out of steam – this diagnosis by Bruno Latour is crucial for the “Manifesto for post-critical education” as well as for the on_education issue “The Fatique of Critique?”. With this essay, we contradict Latour's diagnosis. Latour’s polemic against critique is based firstly on a questionable diagnosis of our time and secondly on a general and programmatic critique of sociology. Against that, we bring out two main points. The first insight highlights that change is initially dependent on variations that can only arise from a negation of the existing. The second insight comes from the sociology of critique, which paradoxically sees success in the failure of critique.

Empirische Bildungsforschung als Rechtfertigung rechtspopulistischer Angst. Zur gegenwartsdiagnostischen Verwendung von Large-Scale-Assessments - Haker, Christoph; Otterspeer, Lukas (Erziehungswirklichkeiten in Zeiten von Angst und Verunsicherung)

Kritik rechtspopulistischer Gewissheiten. Für die Öffnung von Kontingenzen moderner Gesellschaftsordnungen - Haker, Christoph; Otterspeer, Lukas (Gewissheit. Beiträge und Debatten zum 3. Sektionskongress der Wissenssoziologie)

Die Beweglichkeit der Kritik: zur Wechselbeziehung von Kontextualisierung und Objektivierung im digitalen Zeitalter - Haker, Christoph; Otterspeer, Lukas (BEHEMOTH. A Journal on Civilisation)

Die Freiheit, ein*e Andere*r zu werden. Eine Bricolage zur Praxis soziologischer Theorie. - Haker, Christoph (Lebendige Theorie)

The multiplicity of halal standards: a case study of application to slaughterhouses - Abdelrahem, Mohammed; Abdallah, Ali; Pasqualone, Antonella (Journal of Ethnic Foods)
Keywords: halal standards; halal food; slaughterhouses

Medien der Sorge, Techniken des Selbst. Praktiken des Über-sich-selbst-Schreibens bei Christoph Schlingensief und Elfriede Jelinek - Degeling, Jasmin

Mein Handy hat schon Covid-19!‘ Digitaler Faschismus unter Bedingung der Corona-Pandemie - Degeling, Jasmin (onlinejournal kultur&geschlecht)

Medien der Sorge. Einleitung in den Schwerpunkt - Degeling, Jasmin; Haffke, Maren (Zeitschrift für Medienwissenschaft. Jg. 13, Heft 24)

Students’ learning of computational thinking in schools with different curriculum approaches including individual student characteristics - Labusch, Amelie; Eickelmann, Birgit (Proceedings of the 5th APSCE International Computational Thinking and STEM in Education Conference 2021)